Some properties of thermostable amylase of four isolates of Bacillus licheniformis - ELHAM S. DAWOOD; SIRAG A. IBRAHIM; SAIFELDIN A.F. EL-NAGERABI (Smujo International, 2015)
Abstract. Dawood ES, Ibrahim SA, El-Nagerabi SAF. 2015. Some properties of thermostable ?-amylase of four isolates of Bacillus licheniformis. Nusantara Bioscience 7: 90-95. Amylases are one of the most important enzymes in the food industry and biotechnology. The present investigation was concerned with the production, purification and partial characterization of extracellular amylase from endogenous Sudanese Bacillus licheniformis isolate namely SUDK1, SUDK2, SUDK4, and SUDO. The extracted enzyme was partially purified using DEAD Sephadex A-25 gel filtration and the enzymatic reaction product was identified using thin layer chromatography. The results revealed that DEAE-Sephadex is an excellent and effective purification method and the activity of the partially purified enzymes (83.343-121.755 U/mg protein) compared to the crude extracts (4.626-7.250 U/mg protein) with increase of up to 16.8-18.3 folds. Amylase enzymes hydrolyze starch forming various maltooligosaccharides, such as maltose as major products and were identified as ?- amylases. The enzyme's activity was optimum at 60-70°C and was active up to 90°C with residual activity of only 30-50%. All enzymes were stable between pH 6.0-9.0 with optimum activity at pH 7.0. The enzymes were stable and retained nearly all of their initial activities at -20°C at the end of 24 weeks and lost less than 60% of their initial activities at 4°C after 8 weeks. The Km values for this enzyme were 1.25-2.0 mg/mL which showed high affinity and needs only small amount of substrate to be saturated. Therefore, these ?-amylases were thermostable at a wide range of temperature and pH values rendering them useful properties in food, feed, textiles, and relevant biotechnological industries.